Determinants Affecting Consumer Complaining Behavoir: A Study in a University of Pakistan - Rizwan, Muhammad; Ali, Syed Hassan; Akhter, Sonia; Abbas, Yasir; Kanwal, Anila; Iqbal, Shoaib; Aziz, Waqas (Asian Journal of Empirical Research, 2013)
The purpose of this conceptual research study paper is to incorporate 2 streams of collected works associated to consumer complaining behavior (CCB) and attitudinal or behavioral perspectives. The conceptual structure aims to enhance or change the viewpoint on consumers’ complaint practices. The generated model is purposed that completes the attitudinal or behavioral perspectives and consumer complaining behavior literature in the framework. Cautious study review with potential has done to validate the conceptual work here. The selected framework is representing an initial point for elaborating concepts on consumer complaining behavior. The organized study of empirical work research is a need to assess the generated integrative model.